Diurnal birds of prey of national nature park ‘Dvorichanskyi’ and adjacent territories - Vysochyn, M.; Banik, M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The studies of species composition and abundance of diurnal birds of prey may be quite indicative of the state of natural ecosystems and of the level of impact of human-induced factors on their functions. Such studies are particularly important within the protected areas taking into account unfavourable conservation status of many species of the group. The status, abundance, aspects of habitat distribution and breeding habitat preferences of diurnal birds of prey were studied within national nature park ‘Dvorichanskyi’ and adjacent territories (750 sq. km, Dvorichanskyi district, Kharkiv Region, Ukraine) in 2010–2018. 22 species were registered. The breeding of six species was confirmed e.g. Black Kite (Milvus migrans), Marsh Harrier (Circus aeruginosus), Goshawk (Accipiter gentilis), Sparrowhawk (Accipiter nisus), Common Buzzard (Buteo buteo), Booted Eagle (Hieraaetus pennatus). The breeding of four more species is considered probable namely Honey Buzzard (Pernis apivorus), Montagu’s Harrier (Circus pygargus), White-tailed Eagle (Haliaeetus albicilla) and Hobby (Falco subbuteo). There are indications of possible breeding of Short-toed Eagle (Circaetus gallicus) and Kestrel (Falco tinnunculus). The rest of the species are migrating and/or wintering. The most numerous breeding species is Common Buzzard. The abundance of Booted Eagle is comparatively high that discerns the study area from other parts of Kharkiv Region. 40 nests of birds of prey were carefully inspected. The majority were found in ravine steppe forests (83%). Oak, alder and willow flood-plain forests are very important breeding habitats for Black Kite and Booted Eagle while ravine steppe forests are those for Goshawk, Sparrowhawk, Common Buzzard and Booted Eagle. Pedunculate oak (Quercus robur) is the most favourable tree species for building the nests (47.5% of all inspected nests) followed by European ash (Fraxinus excelsior) (15%) and European pear (Pyrus communis) (10%).